PERSPEKTIF PENGEMBANGAN AGRIBISNIS MARKISA DI KABUPATEN SOLOK, SUMATRA BARAT - Buharman B; Yanti Mala; Edial Afdi (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2004)
Sweet passion fruit (Passiflora liguralis) plants grow well in Solok district highland. Productive area of theplantation is 3,825 ha with total production of 49,577 tons or equal to Rp 81,802 billions. Passion fruit agribusinessdevelopment in the future considers four aspects of (1) production technology, (2) post harvest, (3) financialfeasibility, and (4) land potential for development. First, two high-yielding varieties of Gumanti and Super Solindahave better characteristics of higher yields, size and quality of fruits, shelf life, and higher selling prices compared tothe variety of ordinary violet flower commonly planted by the farmers. Second, the fruits not qualified for fresh fruitsat household scale could be processed into juice and syrup. Both varieties with certain harvested maturity level andpackaging have longer shelf life for long distance transportation. Third, the farm business was financially feasible asshown by NPV of Rp 26,977,900, B/C ratio of 3.46, and IRR of 40 percent with economic plantation period of 10years. Fourth, there are 10,218 ha of land available for expansion of the plantation in the two main producing subdistricts. In addition, the farmers have planted passion fruit plants in some sub districts in the other highland areas. Allof those aspects are promising, but the policy makers have to pay attention to the aspects of competitive advantageand land conservation. Integrating farm practice improvement, product processing, market enhancement, and landexpansion becomes very strategic in passion fruit agribusiness development as part of regional development.Key words: passion fruit, agribusiness development Markisa manis berkembang baik di wilayah dataran tinggi Kabupaten Solok. Secara ekonomis dari luasareal produktif 3.825 ha dengan produksi 49.577 ton, setara Rp 81.802 milyar/tahun. Perspektif peluangpengembangan agribisnis markisa ke depan, dapat ditinjau dari empat aspek, yaitu: (1) teknologi produksi (2) pascapanen, (3) kelayakan finansial, dan (4) potensi lahan untuk pengembangan. Pertama, dua varietas unggul Gumantidan Super Solinda mempunyai keunggulan berupa daya hasil, ukuran dan mutu buah, daya simpan, serta harga juallebih tinggi dibanding varietas bunga ungu biasa yang banyak diusahakan petani. Selain varietas, teknik pembibitan,dan perbaikan budidaya telah dilakukan. Kedua, untuk buah yang tidak memenuhi syarat sebagai buah meja, dalamskala rumah tangga dapat diolah menjadi jus dan sirup, sedangkan untuk transportasi jarak jauh pada tingkatkematangan panen dan kemasan tertentu daya tahan bisa lebih lama. Ketiga, dari aspek usahatani, budidaya yangdilakukan petani layak secara finansial dengan kriteria NVP=Rp 26.977.900; B/C=3,46; dan IRR>40% dengan umurekonomis 10 tahun. Keempat, pada dua kecamatan sentra produksi utama, terdapat potensi lahan untuk pengembanganseluas 10.218 ha. Selain itu, markisa juga telah dikembangkan oleh masyarakat pada beberapa kecamatan wilayahdataran tinggi lainnya. Semua aspek tersebut sangat mendukung, namun demikian tingkat keunggulan kompetitif sertaaspek konservasi lahan untuk pengembangan perlu mendapat perhatian. Keterpaduan dalam perbaikan budidaya,pengolahan produk, perluasan pasar dan areal menjadi sangat strategis untuk pengembangan agribisnis markisasebagai bagian dari pengembangan wilayah.Kata kunci : markisa, pengembangan, agribisnis